Web Design and Web Brand Image of Online Travel Agent: Its Effect on Purchase Intention Mediated by Trust - Putri Daniela Christine Farida Uli; Dwinita Laksmidewi (International Journal of Science and Society, 2023)
E-ticketing and online booking have transformed the aviation industry, hospitality, travel agencies and consumer behavior by providing new ways of communication and service support. Hence, the quality of e-ticketing and online booking websites is an important factor to drive the business. This study aims to analyze the effect of web information design, web visual design, and web brand image on purchase intentions mediated by trust. The data were obtained by conducting a survey to the community using the Online Travel Agent (OTA) website in the DKI Jakarta area. Hypothesis testing uses Structural Equation Model (SEM) analysis with SmartPLS. The results show that web information design has a direct effect on trust but has no significant effect on purchase intention either directly or mediated by the trust variable, web brand image has an effect on purchase intention mediated by trust, while web visual design has no effect on trust or purchase intention.